Reproducibility of pacing strategies in high level junior swimmers - Skorski, S.; Faude, O.; Rausch, K.; Meyer, T. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Recently, the analysis of pacing strategies has gained importance in sports medicine research. Up to now, there is little data available in swimming. Three different ways of pacing have been described in swimmers: even, fast-slow and slow-fast pacing (Maglischo, 2003). This classification was mainly developed from observations in races at Olympic Games or World Championships. The aim of this study was to determine the reproducibility of pacing strategies in high level junior swimmers during 200, 400 and 800 m tests. METHODS: 16 competitive front crawl swimmers (7 , 9 , age: 16.9±2.2 years, training history: 6±1.8 years) performed 200, 400 and 800 m tests, each distance twice, within one week. All 100m split as well as total times were recorded for the 800 and 400 m test (50m split times for the 200m test). Furthermore blood lactate concentrations [bLa] were measured after each test. Training and nutrition on test days and the day before were tightly controlled. RESULTS: Pearson correlations as well as Bland-Altman analyses were used to determine reproducibility. Correlation coefficients (r) for the 800 m were between r = 0.83 and 0.97 for all split times, except for the last section (r = 0.79). Mean bias was between 0.13 and -0.81s, the limits of agreement [LoA] were between ± 1.7 and 5.0 s for all 100 m sections except the final one (mean bias = -1.05 s, LoA = 5.8 s). During the 400 m race r was above 0.90 for each section (mean bias = -0.16 to -0.60 s, LoA = ± 1.6 to 4.7 s). Results were similar during the 200m (r > 0.90, mean bias = -0.35 to -1.14 s, LoA = ± 1.1 and 2.6 s). For [bLa] was r was 0.88 during 800m and 0.80 during 400 m, whereas for the 200 m it was 0.32. DISCUSSION: The reproducibility of pacing profiles of junior swimmers seems acceptable, although the last section shows greater variability. Thus it might be speculated that anticipatory control of intensity is dominant during the race with actual sensory feed-back information getting more important during the end spurt of the race. However, the physiological rational behind pacing strategies is mostly unknown and further research is needed.